State Policy Making on Coffee International Trade Commodities - Dodi Sukmayana (Universitas Sultan Ageng Tirtayasa, 2022)
This research will be carried out to find out how the trade balance of coffee commodities in Indonesia, the impact of international trade policies on domestic coffee commodity prices, the development of export and import processes for coffee commodities, and international trade policies for coffee commodities in Indonesia will be affected. This study will use a qualitative approach through descriptive methods with data from research and previous studies relevant to this research. This study found that there were fluctuations in the coffee export process in Indonesia, with a tendency for an increase. Meanwhile, in the import process itself, the fluctuations tend to be quite sharp, although there is a similar tendency to continue to increase. In the trade balance, it was found that the export volume of coffee commodities in Indonesia was higher than the value of the volume of imports. The coffee commodity could become one of the largest foreign exchange earners for the Indonesian state.